2021
DOI: 10.1002/mp.15043
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reproducibility of CBCT‐derived radiomics features using a novel three‐dimensional printed phantom

Abstract: Purpose Radiomics modeling is an exciting avenue for enhancing clinical decision making and personalized treatment. Radiation oncology patients often undergo routine imaging for position verification, particularly using LINAC‐mounted cone beam computed tomography (CBCT). The wealth of imaging data collected in modern radiation therapy presents an ideal use case for radiomics modeling. Despite this, texture feature (TF) calculation can be limited by concerns over feature stability and reproducibility; in theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Few studies prospectively performed test-retest experiments to investigate repeatability only, but not reproducibility across multiple centers 10–14 . When multiscanner reproducibility was assessed so far, studies relied on phantom measurements only 15–21 . Phantoms offer precious advantages as known geometry and composition, and allow for limitless measurements under a wide variation of image acquisition parameters.…”
mentioning
confidence: 99%
“…Few studies prospectively performed test-retest experiments to investigate repeatability only, but not reproducibility across multiple centers 10–14 . When multiscanner reproducibility was assessed so far, studies relied on phantom measurements only 15–21 . Phantoms offer precious advantages as known geometry and composition, and allow for limitless measurements under a wide variation of image acquisition parameters.…”
mentioning
confidence: 99%
“…For the evaluation of inter-machine analysis, previous studies reported that there are limitations to performing multi-institutional radiomics analysis because inter-machine differences reduce feature reproducibility. 16,17 Our results also showed that feature reproducibility was lower for different types of machines (Halcyon vs. TrueBeam) than for the same types of devices (TrueBeam vs. TrueBeam), even when using the same image reconstruction algorithm (Figure 4). One possible reason for this is that the anti-scatter grid is different: 15:1 for Halcyon and 10:1 for TrueBeam.…”
Section: Discussionmentioning
confidence: 58%
“…Several researchers have previously designed radiomics phantoms and investigated the repeatability and reproducibility of kV-CT-based radiomic features to establish a basis for analysis. [27][28][29][30] Similarly, although radiomics phantom studies also identified that differences in treatment machines decreased the reproducibility of radiomic features on kV-CBCT, 16,17 there were some concerns regarding their phantom design and lack of external validations. To address these issues, the proposed radiomics phantom simulates a patient's body shape and is sufficiently long in the SI direction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations